Tamsulosin versus Fluid Therapy in Management of Ureteric Stone: A Comparative Study - Adhikari, Bimarsh; Kidwai, Roman (Journal of Nepalgunj Medical College, 2022)
Introduction: Almost all ureteric stone migrates from kidney. The drugs commonly used to assist in the passage of bigger calculi include alpha-blockers, calcium channel antagonists, phosphodiesterase inhibitors, corticosteroids. Tamsulosin is an alpha-1 adrenergic receptor antagonist known to augment the stone expulsion rate. Aims: To evaluate the efficacy of Tamsulosin versus fluid therapy in management of urolithiasis. Methods: The study was carried out on 100 patients (divided into 2 groups) at Nepalgunj Medical college Hospital Nepalgunj from May 2020 to April 2021,between 18-50 years of age of either sex, presenting with a symptomatic urinary calculus as demonstrated on imaging. Group 1 received 0.4mg of tablet tamsulosin once daily for 4 weeks, whereas Group 2 fluid therapy for a period of 4 weeks or until expulsion of stone. Results: Group A reflected 88% (40 patients) expulsion rate, whereas Group B reflected 72.0% (36 patients) expulsion rate. There was a statistically significant difference in the expulsion rate amongst both the groups. 92.0% (46 patients) subjects in Group A demonstrated stone expulsion within 4 weeks, mean time being 8 days. In comparison only 70.0% (35 patients) subjects in Group B demonstrated stone expulsion within 4 weeks, mean time being 14 days.Use of tablet diclofenec 100mg was lower in Group A in comparison to Group B. Conclusion: Tamsulosin is a safe and effective pharmacological agent in management of ureteric stones as it known to increase overall stone expulsion rate, reduced stone expulsion time, decrease acute attacks by acting as a spasmolytic, and fewer pain episodes. It may be considered as a conservative therapeutic option before more invasive procedures like ureteroscopic removal or Extracorporeal shock wave lithotripsy.